2022
DOI: 10.1093/nop/npac016
|View full text |Cite
|
Sign up to set email alerts
|

Do neurocognitive impairments explain the differences between brain tumor patients and their proxies when assessing the patient’s IADL?

Abstract: Background Neurocognitive impairments are common among brain tumour patients, and may impact patient’s awareness of performance in instrumental activities in daily life (IADL). We examined differences between patient- and proxy-reported assessments of the patient’s IADL, and whether the level of (dis)agreement is associated with neurocognitive impairments. Methods Brain tumour patients and their proxies completed the phase 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Importantly, in this review, we did not focus on family caregiver reports, which can substantially differ from patient self-reports, especially when cognitive impairment results in reduced self-awareness of functioning. 37 Still, patients self-reported that changes in personality/behavior, difficulties with communication, concentration, processing speed, and decision-making abilities impact their everyday life. This appeared linked to social functioning, including feelings of isolation and employment issues.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in this review, we did not focus on family caregiver reports, which can substantially differ from patient self-reports, especially when cognitive impairment results in reduced self-awareness of functioning. 37 Still, patients self-reported that changes in personality/behavior, difficulties with communication, concentration, processing speed, and decision-making abilities impact their everyday life. This appeared linked to social functioning, including feelings of isolation and employment issues.…”
Section: Discussionmentioning
confidence: 99%
“…Develop standards for optimal proxy selection Evidence from concordance studies suggests that primary family caregivers are better proxies than clinician caregivers in oncology 4,22,33 However, if there are multiple primary family caregivers, it is not clear which caregiver should report, and collecting multiple proxy reports 39 can pose logistical, budgetary, and interpretation challenges Collecting reasons for proxy report (eg, too ill, not cognitively able) should be considered when reasons vary Develop standards for collection of relevant data about proxies Evidence from pediatric 5 and adult oncology 42 suggests that proxy-related factors are associated with proxy reports and thus should be considered for collection More research is needed to determine other factors that may be relevant 39 and enable the development of recommendations and standards for data collection Identify ways to improve proxy reports Better communication has been suggested as a way to improve proxy symptom reporting, 34 but research in the area is scarce Approaches to improve proxy reports can improve the quality of data in oncology research and clinical care Determine when a proxy or a patient is the more reliable reporter, particularly in situations of cognitive impairment Proxy-patient concordance is suboptimal for patients with cancer who have cognitive impairment, [29][30][31] but it is not clear if the proxy or the patient is more reliable Age-based criteria have been used to guide the choice of reporter in pediatrics 43,44 For adults, examples outside oncology on the basis of cognitive impairment 45 may be relevant, but more work is needed…”
Section: Study Design and Data Collectionmentioning
confidence: 99%
“…28 Of concern are findings of lower patient-proxy agreement in adults with glioma who are cognitively impaired. [29][30][31] Collection of both proxy and patient reports is suggested for cognitively impaired patients, 31,32 but the question of how best to triangulate information across reporters and if proxies or patients are more reliable remains.…”
Section: Concordancementioning
confidence: 99%
See 2 more Smart Citations